(untitled) (Revista Eixos Tech, 2025)
Kombucha is a fermented beverage of Chinese origin produced from the infusion of black or green tea from the Camelia sinensis plant, sugar and a symbiotic culture known as SCOBY. After fermentation, the drink becomes rich in natural nutrients with functions that are beneficial to health such as organic acids, amino acids, vitamin C, polyphenols and antibiotic substances. The present work aims at carrying out a study of the economic feasibility of opening a micro-industry for the production of a black tea kombucha flavored with passion fruit from the caatinga. The caatinga passion fruit is a species native to the dry areas of northeastern Brazil. This fruit is rich in flavonoids, vitamin C and carotenoids, which have antimicrobial and antioxidant properties. For the development of the study, specifications of processes, equipment and analysis of financial and economic indicators were carried out. The evaluation of the investments was carried out using the internal rate of return (IRR), minimum attractiveness rate (TAM), net present value (NPV), simple payback and discounted payback methods. The initial investment for the production of 2,000 L of kombucha flavored with passion fruit from the caatinga was R 187,199.78. The economic indicators obtained resulted in NPV of R 253,154.68, IRR of 22%, TAM of 13.34% p.a. and simple payback of 3.9 years considering a useful life of 10 years. The positive IRR reflects that the enterprise is economically viable and profitable, making it possible to invest and generate income for cooperatives and family farmers.